Within-island diversification in a passerine bird. Issue 1923 (25th March 2020) - Gabrielli, Maëva; Nabholz, Benoit; Leroy, Thibault; Milá, Borja; Thébaud, Christophe
Abstract : The presence of congeneric taxa on the same island suggests the possibility of in situ divergence, but can also result from multiple colonizations of previously diverged lineages. Here, using genome-wide data from a large population sample, we test the hypothesis that intra-island divergence explains the occurrence of four geographical forms meeting at hybrid zones in the Reunion grey white-eye ( Zosterops borbonicus ), a species complex endemic to the small volcanic island of Reunion. Using population genomic and phylogenetic analyses, we reconstructed the population history of the different forms. We confirmed the monophyly of the complex and found that one of the lowland forms is paraphyletic and basal relative to others, a pattern highly consistent with in situ divergence. Our results suggest initial colonization of the island through the lowlands, followed by expansion into the highlands, which led to the evolution of a distinct geographical form, genetically and ecologically different from the lowland ones. Lowland forms seem to have experienced periods of geographical isolation, but they diverged from one another by sexual selection rather than niche change. Overall, low dispersal capabilities in this island bird combined with both geographical and ecological opportunities seem to explain how divergence occurred at such a small spatial scale.